Finding and Conjuring. Issue 8 (17th November 2018) - Pinto, Sarah
ABSTRACT: In considering the persistent ways that haunting, as a metaphoric operation, informs our attentions to history and human experience, this article introduces this special issue by asking what qualities of knowing, reading, and understanding, and what particular histories, might be rolled into "ghostliness." Infrastructural hauntings at once jog the fixity of certain metaphors and help us world our analytics. With the aid of a recent feature film (Session 9) that draws fear from the infrastructural ruins of a haunted hospital, I propose contrasting modes of attending to ghosts in the world and the world in ghosts–finding and conjuring, in which finding sees ghosts as something, while conjuring sees ghosts as always, inevitably, something else. With ghosts and ghostliness at hand, how might we, as anthropologists, consider the unspoken imperatives of our metaphors? How might we invite a localizing turn into our own efforts, being attentive to the ways our analytics propel ways of knowing into the world?